(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Cystic echinococcosis is caused by the larva stage of the parasite, Echinococcus granulosus. CE is one of the most important zoonotic parasitic disease of the Middle East region. This includes the country of Iraq, where CE is known to be present in high levels. The southern province of Al Muthanna in Iraq has limited community-level statistics despite many years of surgical intervention. Objectives: To examine the incidence/demographics of surgically confirmed cases of hydatidosis (hydatid disease), the organs involved with hydatidosis and the occupational risk factors of patients treated surgically for hydatid disease in the city of Al Samawa, Iraq. Methods: A retrospective hospital study was conducted using data from operative reports on patients who were treated surgically for hydatid cyst removal at Al Hussein Teaching Hospital in Al Samawa from January 1, 2018 through December 31, 2018. Data collected from 80 patients included patient gender, age, occupation and the anatomical location(s) involved with the hydatid cysts. The data was analyzed using descriptive statistics. Results: The overall number of surgically confirmed cases studied (n=80) included 62 female and 18 male patients. This produced a female-to-male ratio of 3.4:1. The peak age group of the female patient cohort was 31-40 years and the peak age group of the male patient cohort was 41-50 years. The predominant organ involved was the liver (75%), followed by: lung (10%), peritoneum (5%), spleen (5%), brain (2.5%) and ovary (2.5%). The largest occupational group of patients were housewives (47.5%), while the second largest group were agricultural workers (17.5%). Conclusions: There continue to be a significant number of cases of hydatidosis in Al Samawa City, Iraq. Given the predominant female population age 31-40 at high risk and who are dealt with high numbers of interactions with dogs and agricultural live-stock (given that their occupational assignment is consistently as housewives), targeted public health education with respect to hydatidosis, broader animal vaccination programs and improved management of free-roaming (stray-type) dogs must occur.